Post-Market Surveillance Assessment of the Clinical Accuracy of a Blood Glucose Monitoring System with an Improved Algorithm for Enhanced Product Performance. (January 2023) - Setford, Steven; Liu, Zuifang; McColl, David; Phillips, Stuart; Cameron, Hilary; Grady, Mike
Background: On-going manufacturer-led post-market surveillance (PMS), assessing the clinical accuracy of blood glucose monitoring (BGM) systems, is critical to substantiate the performance of such products for people with diabetes. Materials and Methods: Batches of Verio test-strip product were randomly and routinely selected over the period from launch of an improved-algorithm product to reporting date and sent to 3 clinic sites for clinician-led accuracy assessment. Accuracy is reported as per recently adopted FDA guidance for BGM systems, EN ISO 15197:2015 and MARD/MAD (Mean absolute relative difference/Mean absolute difference). Results: Thirty-three individual test-strip batches were evaluated corresponding to 506 unique donors. Accuracy performance - FDA: 98.9% of values within ±15% of comparator; ISO: 99.0% within ±15 mg/dL or ±15% at <100 mg/dL (<5.55 mmol/L) or ≥100 mg/dL (≥5.55 mmol/L) glucose, respectively. Overall MARD was 4.19% with a MARD range of 3.54%-5.73% across all test strip batches. Conclusions: This post-market surveillance program demonstrates the new BGM system consistently meets measures of clinical accuracy specified by regulators. This program supports a growing demand by regulators for real-world evidence demonstrating consistent in-market product efficacy as opposed to the current largely passive approach that relies on assessment of reports filed by device users.